An Exploration of the Role of Sugar-Sweetened Beverage in Promoting Obesity and Health Disparities - Sigala, Desiree M. (Curr Obes Rep, 2021)
PURPOSE OF REVIEW: The mechanistic role of sugar-sweetened beverage (SSB) in the etiology of obesity is undetermined. We address whether, compared to other foods, does consumption of SSB (1) automatically lead to failure to compensate for the energy it contains? (2) fail to elicit homeostatic hormone responses? (3) promote hedonic eating through activation of the brain’s reward pathways? We followed the evidence to address: (4) Would restriction of targeted marketing of SSB and other unhealthy foods to vulnerable populations decrease their prevalence of obesity? RECENT FINDINGS: The data are lacking to demonstrate that SSB consumption promotes body weight gain compared with isocaloric consumption of other beverages or foods and that this is linked to its failure to elicit adequate homeostatic hormone responses. However, more recent data have linked body weight gain to reward activation in the brain to palatable food cues and suggest that sweet tastes and SSB consumption heightens the reward response to food cues. Studies investigating the specificity of these responses have not been conducted. Nevertheless, the current data provide a biological basis to the body of evidence demonstrating that the targeted marketing (real life palatable food cues) of SSB and other unhealthy foods to vulnerable populations, including children and people of color and low socioeconomic status, is increasing their risk for obesity. SUMMARY: While the mechanisms for the association between SSB consumption and body weight gain cannot be identified, current scientific evidence strongly suggests that proactive environmental measures to reduce exposure to palatable food cues in the form of targeting marketing will decrease the risk of obesity in vulnerable populations.